2022
DOI: 10.1186/s12905-022-01912-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study on serum miR-222-3p and glucose and lipid metabolism in patients with polycystic ovary syndrome

Abstract: Objective microRNAs (miRNAs) play pivotal roles in polycystic ovary syndrome (PCOS), an endocrine and metabolic disorder that commonly occurs in women of childbearing age. This paper aimed to measure miR-222-3p expression in sera of PCOS patients and to explore its clinical value on PCOS diagnosis and prediction of diabetic and cardiovascular complications. Methods Totally 111 PCOS patients and 94 healthy people were recruited and assigned to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, high miR-222-3p expression exhibits a positive relation to FPG in patients with GDM, T2DM, and PCOS. 8–10 Consistently, in T2DM patients treated with metformin, reduced miR-222 in the PB positively correlates with the reduction of FPG and HbA1c. 6 Nevertheless, in patients suffering T2DM and PCOS, high miR-222-3p expressions report lower HDL-C. 10 All these conformed to our study results.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, high miR-222-3p expression exhibits a positive relation to FPG in patients with GDM, T2DM, and PCOS. 8–10 Consistently, in T2DM patients treated with metformin, reduced miR-222 in the PB positively correlates with the reduction of FPG and HbA1c. 6 Nevertheless, in patients suffering T2DM and PCOS, high miR-222-3p expressions report lower HDL-C. 10 All these conformed to our study results.…”
Section: Discussionmentioning
confidence: 76%
“…MiR-222-3p is a highly conserved miRNA mainly expressed in bladder, prostate, lung, ovary, adipose tissue, thyroid, bronchus, islet, skin, and other tissues. 5 Studies have found an increasing miR-222-3p expression in the peripheral blood (PB) of patients suffering type 2 diabetes mellitus (T2DM), 6 obesity, 7 polycystic ovary syndrome, 8 and gestational diabetes mellitus. 9 According to a cohort follow-up study, miR-222-3p overexpression in the mononuclear cells of PB raises the risk of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…2011 ). Cryptotanshinone lessens the combination of androgen with the androgen-receptors present in the sebaceous glands and inhibits the sebaceous glands from secreting acne caused by the sebaceous glands of the hair follicle (Wang N 2015 ). In summary, constituents absorbed into blood of QCF contain antibacterial, anti-inflammatory and anti-androgen components.…”
Section: Discussionmentioning
confidence: 99%